Quantifying multi-regional indirect economic losses: An assessment based on the 2021 rainstorm events in China - Liu, Yuan; Li, Ying; Wang, Guofu; Gao, Ge; Chen, Yixiao (Frontiers in Earth Science, 2023)
Quantitative assessment of economic losses from disasters can benefit government decision-making as well as mitigation and adaptation strategies. Here, we identified significant rainstorm events in China in 2021 using an objective identification method and investigated the direct economic losses (DELs) from each event. Then, a loss assessment model was developed to estimate the indirect economic losses (IDELs) from rainstorm events. We found that, in 2021, China experienced 36 major rainstorm events, causing approximately 179.8 billion yuan in DELs. The north of China was severely affected by rainstorms and floods, with Henan, Hebei and Shaanxi being the main loss centers. The assessment of IDELs based on rainstorm events showed a non-linear relationship between direct and indirect losses. The socio-economic impact of the 2021 Henan flood (Event No.15) was the most serious, with direct and indirect losses of 125.8 billion yuan and 269.1 billion yuan, respectively. The primary industry in Henan was seriously affected, and the impact also spread to Inner Mongolia and Guangdong, causing indirect losses of 23.9 billion and 13.1 billion yuan, respectively. We recommend that the indirect losses resulting from such interregional trade linkages should be considered in catastrophe risk management. Finally, the sensitivity analysis showed that moderate overproduction can reduce the indirect impacts caused by disasters. A more detailed study is required to explore how to determine the appropriate levels of disaster relief, as well as a rational funding allocation mechanism.